2023
DOI: 10.1186/s12889-022-14859-2
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of maternal health education and maternal screening on knowledge and the uptake of infant screening for sickle cell disease in Dar-Es-Salaam, Tanzania; a quasi experimental study

Abstract: Background Globally, Sickle cell disease (SCD) is one of the most common genetic disease with high childhood mortality. Early identification of babies with SCD through newborn screening (NBS) and linking them to care are among the recommended interventions. The purpose of this study was to assess the efficacy of maternal health education and maternal screening for SCD on knowledge and the uptake of infant screening for SCD among mother-infant pairs attending antenatal clinics at Government heal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
1
0
2
Order By: Relevance
“…A 2022 report of a study of POC tests (HemoTypeSC TM and SickleSCAN ® ) showed reliability of either versus IEF, and both were found to be acceptable for screening [ 1577 ]. A 2023 report of a study at three hospitals in Dar-Es-Salaam reported that maternal health education and maternal screening for SCD were feasible and efficacious interventions to increase the knowledge and uptake of NBS, and these interventions were strongly recommended for inclusion in comprehensive care packages for pregnant women attending antenatal clinics [ 1578 ].…”
Section: Resultsmentioning
confidence: 99%
“…A 2022 report of a study of POC tests (HemoTypeSC TM and SickleSCAN ® ) showed reliability of either versus IEF, and both were found to be acceptable for screening [ 1577 ]. A 2023 report of a study at three hospitals in Dar-Es-Salaam reported that maternal health education and maternal screening for SCD were feasible and efficacious interventions to increase the knowledge and uptake of NBS, and these interventions were strongly recommended for inclusion in comprehensive care packages for pregnant women attending antenatal clinics [ 1578 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pada penelitian ini, pendidikan kesehatan yang diberikan dalam bentuk ceramah, diskusi dan demonstrasi dengan menggunakan media slide power point serta leaflet tentang upaya pencegahan dan cara menghadapi banjir. Pendidikan Kesehatan dapat bermanfaat untuk mendorong para responden yang mendapatkan pendidikan kesehatan untuk berbagi pengetahuan dengan orang lain karena hal ini meningkatkan pengetahuan pribadi mereka (Tutuba et al, 2023). Di sisi lain, pendidikan kesehatan adalah suatu cara untuk memberikan informasi, pengetahuan dan pemahaman tentang kesehatan untuk merubah pola pikir individu atau masyarakat menjadi tahu dan merubah perilaku hidup ke arah yang lebih baik untuk menjaga kualitas hidupnya (Taviyanda;, Richard;, & Rimawati, 2022).…”
Section: Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan Dan Sikap...unclassified
“…Terjadi juga peningkatan secara signifikan untuk persentase jawaban yang benar pada post test setelah responden diberikan booklet tentang informasi demam berdarah (p<0,05) (AhbiRami & Zuharah, 2020). Literatur ini sesuai dengan literatur yang lain juga bahwa pengetahuan meningkat ketika populasi studi disediakan materi pendidikan kesehatan (Tutuba et al, 2023). Program pendidikan kesehatan secara signifikan meningkatkan pengetahuan dan praktik tentang banjir di daerah tergenang dan pengetahuan hanya di daerah tidak tergenang (P<0,05) (AhbiRami & Zuharah, 2020).…”
Section: Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan Dan Sikap...unclassified